Adaptive behavior in infants and toddlers with Down syndrome and fragile X syndrome. Issue 3 (5th February 2018) - Will, Elizabeth A.; Caravella, Kelly E.; Hahn, Laura J.; Fidler, Deborah J.; Roberts, Jane E.
Abstract : Individuals with Down syndrome (DS) experience deficits across all domains of adaptive functioning, however little is known about the emergence and age‐related changes of these impairments compared to other neurogenetic disorders with similar intellectual disability impairments, such as fragile X syndrome (FXS). Adaptive behavior is key for optimal functioning in these populations. Participants aged 5–45 months comprised three age‐matched groups, DS ( n = 64), FXS ( n = 69), and typically developing controls (TD; n = 69). Adaptive behavior was measured on the Vineland Adaptive Behavior Scales‐II. Regressions were used to examine adaptive behavior in a cross‐sectional design across age. DS infants and toddlers evidenced deficits across all areas of adaptive behaviors compared to the age‐matched TD group, with clear impairments present in the first year of life. Motor skills were the area of greatest weakness in children with DS with significant impairment evident at 12 months of age that remained low through 3 years. Compared to age‐matched children with FXS, children with DS showed initially lower standard scores at 12 months of age, but slower declines in standard scores across age, resulting in less impaired functioning at 36 months. This is the first study to compare adaptive behavior in infants and toddlers with DS to FXS, and demonstrate the phenotypic specificity of adaptive profiles in this diagnostic group. These findings provide evidence that adaptive behavior should be a major target of intervention in children with FXS and DS, and that these differences are potentially driven by unique etiologies attributable to each disorder.